Usos do binômio de Newton em diferentes contextos - Silva, Paulo Henrique da [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Isaac Newton was born on December 25, 1642 and entered college at Trinity College in 1661, until then had not had much contact with Mathematics. He was influenced by renowned mathematicians such as Euclid, William Oughtred, and Lucasian Chair of Mathematics Isaac Barrow, who were instrumental in the success of his research. This qualitative study aimed to carry out a brief study of the work of Isaac Newton under the aspect of Mathematics, to understand the mathematical development, related especially to the Binomial, which bears his name. The work is based on the methodology of exploratory bibliographical research and we focus on the central question: Where can we use Newton's binomial?. In order to understand this Binomial, examples of use are presented in Biology, Informatics, Probability present in the lottery games and in the process of security of vestibular tests, being the last one to hinder fraud in admission to university education

Isaac Newton nasceu em 25 de dezembro de 1642 e ingressou nos estudos universitários no Trinity College, em 1661, até então não tivera muito contato com a Matemática. Sofreu influência de renomados matemáticos como Euclides, William Oughtred e o professor Lucasiano Isaac Barrow, os quais foram determinantes para o sucesso de suas pesquisas. Este trabalho, de cunho qualitativo, teve como objetivo realizar um breve estudo da obra de Isaac Newton sob o aspecto da Matemática, entender o desenvolvimento matemático, relacionado especialmente ao Binômio, o qual leva o seu nome. O trabalho é pautado na metodologia de pesquisa bibliográfica exploratória e nos orientamos na questão central: Onde poderemos empregar o Binômio de Newton?. Para entender o referido Binômio são apresentados exemplos de utilização na Biologia, Informática, Probabilidade presente nos jogos de loteria e no processo segurança de provas de vestibulares, sendo o último para dificultar fraudes na admissão no ensino universitário
Keywords: Newton, Isaac 1642-1727; Matemática; Ensino médio; Analise combinatoria; Mathematics